THE EFFECTIVENESS OF DISCOVERY-DISCUSSION TECHNIQUE IN VOCABULARY TEACHING. AN EXPERIMENTAL RESEARCH IN INTERMEDIATE-TWO LEVEL CONVERSATION PROGRAM - Bahri, Saeful (Language Circle: Journal of Language and Literature, 2009)
The objective of this research is to find out whether or not the combination of discussion and discovery technique gives better effect to the students vocabulary mastery than that of vocabulary-drill discussion technique. Based on review of related theories, the proposed hypothesis of this research is as follows: The use of discovery-discussion technique gives a positive and significant effect in improving intermediate-two level students vocabulary mastery better than that of vocabulary-drill discussion one. The population of this research is all intermediate-two level students of Conversation Program at Global Lingua English course Tegal. For the purpose of this research, I randomly took eighteen out of fifty-five students as the research sample which were then grouped into two groups (with equal number of students in each group), the experimental group and the control group. I used vocabulary tests in the form of multiple choice with four options as the research instrument. The analysis of the data is done using t-test. And from the computation using SPSS, it shows that the result of t-test is 2.645 while t-table with degree of freedom (d.f) is 16 in the level of significance of 5% is 1.745.ÃÂ  Thus, Ha is accepted and Ho is rejected because t-ratio is higher than t-table ( 2.645 < 1.745). Based on the result of the above analysis, it can be inferred that the discovery-discussion technique does give better and more significant effect than the vocabulary-drill discussion one in improving intermediate Ã¢â¬â two studentsÃ¢â¬â¢ vocabulary mastery in a conversation class. ÃÂ  Key Words: Intermediate-two level, vocabulary mastery, Discovery-Discussion combination technique, conversation class